Effect of various Na/K ratios in low-salinity well water on growth performance and physiological response of Pacific white shrimp Litopenaeus vannamei - 刘泓宇 谭北平 杨金芳 林颖博 迟淑艳 董晓慧 杨奇慧 (Chinese journal of oceanology and limnology, 2014)
To investigate the influence of sodium to potassium （Na/IO ratios on the growth performance and physiological response of the Pacific white shrimp （Litopenaeus vananmei）, various concentrations of KC1 were added to low-salinity well water （salinity 4） in an 8-week culture trial. Six treatments with NWK ratios of 60：1, 42：1, 33：1, 23：1, 17：1, and 14：1 were replicated in triplicate. The highest weight-gain rate （3 506±48）% and survival rate （89.38±0.88）% was observed in well water with Na/K ratios of 23：1 and 42：1, respectively, while the feed conversion ratio （1.02～0.01）, oxygen consumption, and ammonia-N excretion rate was the lowest in the medium with a Na/K ratio of 23：1. Gill Na＋-K＋-ATPase activity, as an indicator of osmoregulation, peaked in the treatment where the Na/K ratio was 17：1. The total hemocyte count, respiratory burst, and immune-related enzyme activities （ALP, LSZ, PO, and SOD） ofL. vananmei were affected significantly by Na/K ratios （P〈0.05）. After challenged with Vibrio harveyi, the cumulative mortality of shrimp reared in a Na/K ratio of 23：1 （30±14.14）% was significantly lower than the control （75～7.07）%. In conclusion, the addition of K＋ to low-salinity well water in L. vannamei cultures is feasible. Na/K ratios ranging from 23：1 to 33：1 might improve survival and growth. Immunity and disease resistance are also closely related to the Na/K ratio of the low-salinity well water. The findings may contribute to the development of more efficient K^＋ remediation strategies for L. vananmei culture in low-salinity well water.